Progress and Visions in Quantum Theory in View of Gravity 2020
DOI: 10.1007/978-3-030-38941-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Snyder-de Sitter Meets the Grosse-Wulkenhaar Model

Abstract: We study an interacting λ φ 4 ⋆ scalar field defined on Snyder-de Sitter space. Due to the noncommutativity as well as the curvature of this space, the renormalization of the two-point function differs from the commutative case. In particular, we show that the theory in the limit of small curvature and noncommutativity is described by a model similar to the Grosse-Wulkenhaar one. Moreover, very much akin to what happens in the Grosse-Wulkenhaar model, our computation demonstrates that there exists a fixed poin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…It is therefore naturally of interest to further investigate the origin of the harmonic term. It has been observed that the introduction of such term may be justified by the assumption of a de Sitter spacetime background [12]. For this reason, we extend our previous study of the Snyder scalar QFT to the case of a de Sitter background.…”
Section: Introductionmentioning
confidence: 80%
“…It is therefore naturally of interest to further investigate the origin of the harmonic term. It has been observed that the introduction of such term may be justified by the assumption of a de Sitter spacetime background [12]. For this reason, we extend our previous study of the Snyder scalar QFT to the case of a de Sitter background.…”
Section: Introductionmentioning
confidence: 80%
“…For example, it is clear from (4) that the uncertainty relations for ∆x i ∆p j in the Weyl realization depend on the expectation values of the tensorial degrees of freedom, while in the classical realization (5) they coincide with those of the standard Snyder model. Also, modifications to the Casimir force between conducting plates could be evaluated on the lines of the calculations performed in [26] for the standard case.…”
Section: Discussionmentioning
confidence: 99%
“…and the interaction term becomes V = Mω 2 8 ∑ ij x i p j x i p j − x j p i + x ik p jk x il p jl − x jl p il + 2x i p j x ik p jk − x jk p ik +β −2 x j p ij x k p ik + β 2 x ij p j x ik p k − x i p j p jk x ik − p j x i x ik p jk (26) Defining, for β = 0,…”
Section: Noncovariant Formalismunclassified
“…After several years of an almost total oblivion, these ideas regained vigor with the advent of the 𝑞-deformed Poincaré algebra [12], obtained as a limit of the Drinfeld-Jimbo deformation of the anti-de Sitter algebra so(3, 2). Among the subsequent works devoted to the study of particles and fields in 𝜅-Minkowski and Snyder spaces, we can mention [35,[56][57][58][59][60][61][62][63][64][65][66][67][68] and especially those dealing with fermions [69][70][71][72][73].…”
Section: Fermions In Doubly Special Relativity: a Geometric Waymentioning
confidence: 99%